2012
DOI: 10.1097/id.0b013e31823fcc0f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Polyvinyl Siloxane Technique With Resin-Splinted Transfer Copings Used for Multiple Implant Abutment Impressions

Abstract: Resin-splinted transfer copings in condensation siloxane or irreversible hydrocolloid produced impressions as accurately as polyvinyl siloxane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Most studies had utilized polyether 14,[16][17][18]20,46,50,54,57,65,[74][75][76] (PE) impression material as a stock standard for playing out the accuracy assessment, including different factors, for example, impression system and angle of implant. Among the 17 studies [7][8][9]12,13,19,[39][40][41][42][43][44][45][46][47][48][49] that studied the impression material contrasts, 15 of them looked at polyvinyl siloxane (PVS) and PE impression materials, [7][8][9]12,13,[39][40][41][42][43][44][45][46][47][48] one analyzed vinyl siloxanether (VSE) with PE,19 and another thought about PVS with irreversible hydrocolloid. 49 Most of the studies 12,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies had utilized polyether 14,[16][17][18]20,46,50,54,57,65,[74][75][76] (PE) impression material as a stock standard for playing out the accuracy assessment, including different factors, for example, impression system and angle of implant. Among the 17 studies [7][8][9]12,13,19,[39][40][41][42][43][44][45][46][47][48][49] that studied the impression material contrasts, 15 of them looked at polyvinyl siloxane (PVS) and PE impression materials, [7][8][9]12,13,[39][40][41][42][43][44][45][46][47][48] one analyzed vinyl siloxanether (VSE) with PE,19 and another thought about PVS with irreversible hydrocolloid. 49 Most of the studies 12,…”
Section: Resultsmentioning
confidence: 99%
“…Among the 17 studies [7][8][9]12,13,19,[39][40][41][42][43][44][45][46][47][48][49] that studied the impression material contrasts, 15 of them looked at polyvinyl siloxane (PVS) and PE impression materials, [7][8][9]12,13,[39][40][41][42][43][44][45][46][47][48] one analyzed vinyl siloxanether (VSE) with PE,19 and another thought about PVS with irreversible hydrocolloid. 49 Most of the studies 12,13,[39][40][41][42][43][44][45][46][47][48] have indicated similar precision, with insignificant differences among PVS and PE for multi-implant impressions, however a couple others 7,8 have reported more accuracy with PVS in contrast with PE, but in some circumstances when the implants were placed subgingivally …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,24,27,28,32,38,42,[53][54][55] Assuncao i wsp. 56 dowiedli ponadto, iż nie ma różnic w blokowaniu transferów żywicą akrylową samopolimeryzującą, żywicą świa-tłoutwardzalną oraz wcześniej dostosowaną metalową belką łączącą implanty.…”
Section: Techniki Wyciskoweunclassified